Arnulfo Trejo, pioneer of Hispanic/Latino/Chicano librarianship in the United Sates - Meneses-Tello, Felipe (Revista General de Información y Documentación, 2023)
Abstract The professional profile of Dr. Arnulfo D. Trejo, considered in the United States as the father of Latin librarianship, is analyzed. Trejo was a Mexican-American librarian with a special professional interest in library service to Spanish-speaking Latino communities. He always kept in mind that the profile of the community was essential to study and analyze, both for the systematic development of collections in Spanish and for the management of library and information services with ethnic and multicultural perspectives. As a professor emeritus of library and information science at the University of Arizona, he inspired many people, especially professional librarians, to serve the needs of the Spanish-speaking communities. Based on his work, it can be considered that he was a professional reformer of monolithic library services in the United States; a reformer in the management of intercultural/bicultural library services for marginalized communities; a progressive professor in the field of Latino library education to assist the Spanish-speaking minorities in that country. From a general point of view, Trejo’s work covers three major issues: 1] creation of library services for Spanish-speaking communities, 2] training Hispanic librarians to serve diverse ethnic groups, and 3] supplier of books published in Spanish to be acquired in American libraries. The main aim of this research is to make the work of this Hispanic/Latino/Chicano librarian known among the Ibero-American library community.